Details of identification for Common Moorhen, Glaucous Gull, and Yellow-bellied Flycatcher, Fall 1986 - Cecil, Robert I.et al (1986)
Field notes written by Robert Cecil detailing the sighting of a Common Moorhen near Keokuk, a Glaucous Gull at Saylorville Dam, and a Yellow-bellied Flycatcher at Shimek State Forest. Epson - sheet feed